2006
DOI: 10.1111/j.1745-4522.2006.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Lipids During Alkaline Cooking of Corn

Abstract: The effect of alkaline cooking on corn oil quality characteristics was investigated. This process is used to produce tortillas and snacks. The corn was cooked in a solution of calcium hydroxide at the concentrations of 0.0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0% for 45 min. The oil was then extracted from cooked grains and saponification (SV), iodine (IV) and peroxide (PV) values were determined. Color parameters L and b were also measured. The SV was 85.7 (mg KOH/g oil) in the absence of calcium hydroxide and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
3
6
0
1
Order By: Relevance
“…The results of this particular investigation are consistent with those obtained by Martı´nez-Flores et al (2006), who reported that the IV decreased when alkaline cooking was performed with a concentration of at least 2.5% of Ca(OH) 2 . …”
Section: Iodine Valuesupporting
confidence: 82%
See 2 more Smart Citations
“…The results of this particular investigation are consistent with those obtained by Martı´nez-Flores et al (2006), who reported that the IV decreased when alkaline cooking was performed with a concentration of at least 2.5% of Ca(OH) 2 . …”
Section: Iodine Valuesupporting
confidence: 82%
“…The maximum PV (120.20 meq O 2 /kg oil) was observed at a concentration of Ca(OH) 2 of 0.75% with a steeping time of 8 h; the minimum PV (18.40 meq O 2 /kg oil) was observed at a concentration of 0.75% Ca(OH) 2 with a steeping time of 16 h. In general, high PVs were observed at low steeping times and low concentrations of Ca(OH) 2 (Figure 3) suggesting that as the primary stage of oil oxidation started and the steep time increased, peroxides were converted to secondary oxidation products, and thus the PV decreased. Studies by Martı´nez-Flores et al (2006) indicated that the PV remained relatively constant at a concentration of Ca(OH) 2 of 1.0% in nixtamalized corn oils. However, they found that the PV decreased when the concentration of Ca(OH) 2 increased from 1.5 to 3.0%.…”
Section: Peroxide Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Martı´nez-Flores, Garnica-Romo, Romero, and Yahuaca (2006) reportaron una disminucio´n lineal en el contenido de extracto ete´reo respecto´al contenido de hidro´xido de calcio usado durante el proceso de nixtamalizacio´n. Ellos asocian esta disminucio´n en el contenido de lı´pidos a la pe´rdida de los mismos durante la coccio´n y el reposo del maı´z o bien a que los lı´pidos pueden reaccionar con los iones de calcio para formar materiales in-saponificables que no se pueden extraer de manera eficiente con el disolvente utilizado.…”
Section: Composicio´n Quıḿica De Hco Hpt Y Hcunclassified
“…Nixtamalization, a traditional process of lime cooking and steeping of cereals, particularly maize, is popular in Mexico and Central America, and has been practiced for many years (Bressani et al, 1990;Serna-Saldivar et al, 1990;Martínez-Flores et al, 2002;2006;Rendón-Villalobos et al, 2009). During nixtamalization, many physical (Rodriguez et al, 1996;Almeida-Dominguez et al, 1997), structural (Parades-Lopez andSaharopulos, 1982;Gomez et al, 1989), and chemical (Bedolla & Rooney, 1982;Morad et al, 1986;Serna-Saldivar et al, 1988) changes are known to occur inside the cereal grains.…”
Section: Introductionmentioning
confidence: 99%